Strategi Regulasi Emosi Narapidana Anak di Lembaga Pembinaan Khusus Anak (LPKA) Klas II Tanjung Pati Payakumbuh - Rina Mariana; Maulany Putry Sagita (Psyche 165 Journal, 2019)
This study aims to find out how the emotional regulation strategies of child prisoners in Class II TI LPKA. Pati. Using the one used is Quantitative Descriptive method. Emotional regulation on child inmates was revealed using a questionnaire about emotion regulation strategies. The results of research derived from questionnaires and interviews conducted showed that out of 32 child inmates, as many as 32 child prisoners used emotion regulation strategies cognitive reappraisal in dealing with problems in the LPKA environment. In addition, as many as 7 adolescents have a tendency to use emotion strategies cognitive reappraisal and expressive suppression in dealing with problems in the LPKA environment. Based on the results of the study it was found that 9.37% of child prisoners had poor emotion regulation strategies, and 71.87 % of child inmates have a fairly good emotion regulation strategy and 18.75% have a good emotion regulation strategy.